THE IMPACT OF CIVIL SOCIETY ON THE FORMATION OF SOCIETAL CONSTITUTIONALISM IN THE REPUBLIC OF KAZAKHSTAN (Journal of actual problems of jurisprudence, 2025)
The formation and improvement of the rule of law, democracy is inextricably linked with the development of civil society. The study of the social functioning of the state, the study of the ways of formation of the model of the social state took place in various historical periods. The problem of social support arose a long time ago, but for a long time was not enshrined by law in the Customs and traditions of various societies. Kazakhstan's society has enshrined in the Constitution the direction of creating a stable social policy on a legislative basis.  This is the key to the successful future development of all spheres of life of society and the state. The formation of societal constitutionalism of civil society in the Republic of Kazakhstan is the most important processes reflecting changes in the political, social and legal sphere of the country. It not only clarifies the main points of constitutional principles, but also establishes the guarantee of social rights and freedoms of citizens. Civil society, on the other hand, functions outside the state spheres, being a set of independent public organizations, institutions and initiatives aimed at protecting the rights of citizens and forming public opinion, influencing political, social and economic processes. The presented article is devoted to the study of the influence of civil society on the formation of societal constitutionalism.Keywords: state, civil society, constitutionalism, social state, social.